Analisa Intensitas Cahaya Dan Temperatur Serta Kelembaban Ruangan Digedung C Fakultas Teknik Universitas Riau - Prengki Saputra S; Azridjal Aziz (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The rapid growth of electricity demand is not followed by an increase in electricity supply will trigger an electrical crisis. One effort that can be done to overcome the problem is to save energy. Energy savings can be done with attention to one of the system of light and humidity. Where the system of light and air conditioning is one of the biggest things in the use of electricity by karna it is necessary to do analysis of the intensity of light and humidity room where the analysis is done in Building C Faculty of Engineering, University of Riau. From the calculation of the intensity of light and humidity in Building C Faculty of Engineering University of Riau note that most of the room in Building C Faculty of Engineering, University of Riau has the room temperature and lighting intensity below the standard value. Where for the standard value set for the lighting system is 350 Lux while the light intensity in building c of the riau university engineering faculty is below 350 Lux It should be noted again to improve occupant comfort, light intensity and humidity in Building C Faculty of Engineering can be improved by using lamp energy efficient, ac maintenance routines and also apply energy-saving culture in Building C Faculty of Engineering Keywords : Light intensity, Humidity of the room, Energy Consumption Intensity